Effect of pain-relief nursing on activities of daily living in patients following hip arthroplasty: a systematic review and meta-analysis - Xie, Jun; Bai, Rong; Lei, Hong; Bi, Ruo-Lin; Chen, Ying (Frontiers in Medicine, 2025)
BackgroundDiscomfort and reduced physical function can often be significant after hip arthroplasty procedures, especially in older adults. This can lead to delays in rehabilitation and affect the person’s capability to participate in self-care activities. Nursing care directed toward pain relief may be another meaningful step toward advancement in early mobility and functional independence.PurposeTo conduct a systematic review and meta-analysis to examine the effects of nursing care interventions focused on pain relief on activities of daily living outcomes for participants undergoing hip arthroplasty.MethodsArticles published from January 2010 to December 2023 were identified as a result of searches of the PubMed, Web of Science, and Scopus databases. The inclusion criteria consisted of randomized controlled trials and cohort studies in which nursing care interventions directed toward pain relief were examined against standard care. Random effects models were used to calculate pooled standardized mean differences and 95 percent confidence intervals. The risk of bias assessment was conducted using the Newcastle–Ottawa Scale to evaluate each article included in the study.ResultsFive articles were reviewed and analyzed with a total of 539 patients. Pain relief-focused nursing care interventions, such as individualized patient education, multimodal analgesia, or guided early ambulation, resulted in improved activities of daily living outcomes when compared to standard care. Overall, the pooled effect size was statistically significant, with an indication of overall greater improvement and minimal variability between studies.ConclusionStructured planning through nursing care directed toward pain relief is an effective nursing intervention to achieve and sustain improved functional independence and daily activity outcomes, while also decreasing the experience of pain. Implementing evidence-based nursing interventions can enhance recovery and improve patient satisfaction when used as part of postoperative protocols.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251164478, identifier PROSPERO (CRD420251164478).